Influence of values, beliefs, and age on intention to travel by a new railway line under construction in northern Sweden - Nordlund, A.; Westin, K. (Transportation Research Part A: Policy and Practice, 2012)
The aim is to investigate determinants of intentions to use a new railway line under construction in the northern Sweden. To this end a test was made of a two-part hierarchical model of train-use intentions positing influences from general values and beliefs as well as specific beliefs about the new railway line. A questionnaire was sent to a randomly selected sample of 1238 citizens residing in seven municipalities along the new railway line. In order to also investigate potential generation differences participants were sampled in four age groups, young adults, young middle-aged, middle-aged, and pensioners. The results supported the proposed hierarchical model showing that general values and beliefs influence intentions primarily through the specific beliefs about the railway line. In addition, the results showed that the youngest age group is more open to change and has stronger intentions to use the new railway.